Screening of PRKAR1A and PDE4D in a Large Italian Series of Patients Clinically Diagnosed With Albright Hereditary Osteodystrophy and/or Pseudohypoparathyroidism. (9th February 2016) - Elli, Francesca Marta; Bordogna, Paolo; de Sanctis, Luisa; Giachero, Federica; Verrua, Elisa; Segni, Maria; Mazzanti, Laura; Boldrin, Valentina; Toromanovic, Alma; Spada, Anna; Mantovani, Giovanna
ABSTRACT: The cyclic adenosine monophosphate (cAMP) intracellular signaling pathway mediates the physiological effects of several hormones and neurotransmitters, acting by the activation of G‐protein coupled receptors (GPCRs) and several downstream intracellular effectors, including the heterotrimeric stimulatory G‐protein (Gs), the cAMP‐dependent protein kinase A (PKA), and cAMP‐specific phosphodiesterases (PDEs). Defective G‐protein–mediated signaling has been associated with an increasing number of disorders, including Albright hereditary osteodistrophy (AHO) and pseudohypoparathyroidism (PHP), a heterogeneous group of rare genetic metabolic disorders resulting from molecular defects at the GNAS locus. Moreover, mutations in PRKAR1A and PDE4D genes have been recently detected in patients with acrodysostosis (ACRDYS), showing a skeletal and endocrinological phenotype partially overlapping with AHO/PHP. Despite the high detection rate of molecular defects by currently available molecular approaches, about 30% of AHO/PHP patients still lack a molecular diagnosis, hence the need to screen patients negative for GNAS epi/genetic defects also for chromosomal regions and genes associated with diseases that undergo differential diagnosis with PHP. According to the growing knowledge on Gsα‐cAMP signaling‐linked disorders, we investigated our series of patients ( n  = 81) with a clinical diagnosis of PHP/AHO but negative for GNAS anomalies for the presence of novel genetic variants at PRKAR1A and PDE4D genes. Our work allowed the detection of 8 novel missense variants affecting genes so far associated with ACRDYS in 9 patients. Our data further confirm the molecular and clinical overlap among these disorders. We present the data collected from a large series of patients and a brief review of the literature in order to compare our findings with already published data; to look for PRKAR1A/PDE4D mutation spectrum, recurrent mutations, and mutation hot spots; and to identify specific clinical features associated with ACRDYS that deserve surveillance during follow‐up. © 2016 American Society for Bone and Mineral Research.